Fabrication of fuel saving device helical spring based on gasoline fuel car - Muhammad Ali, Mohamed (2010)
This project is about designing and fabricating fuel saving device based on gasoline fuel car using hydrogen as a additional fuel to saving saving the uses of gasoline fuel which is cannot be recycle and pollute the atmosphere. The main objective of this thesis is suitable due to resent trends in modernization, the standard living has multiplied, there is a heavy demand for the fuels, which is the basis for many industries, factories and automobiles. The device is suitable for gasoline car. Electrolysis process is used to get the hydrogen channeled to the intake manifold. The electrolysis process using water as the electrolyte. The testing were performed on gasoline car engine to get saving efficiency data. Finally, gasoline fuel reducing (volume) versus time (minute) data recorded to be analyse.